Implementasi Sifat Shiddiq Dalam Pelaksanaan Prinsip Transparansi GCG Pada Lembaga Keuangan Syariah - Solikin, Akhmad Bagus; Putra, Muhammad Adam Rizky; Djasuli, Mohammad (CV. ITTC INDONESIA, 2022)
This article aims to provide information about the Implementation of Siddiq Characteristics in the Implementation of the GCG Transparency Principles in Islamic financial institutions. This study uses a literature research research method. The source of the data obtained is by using secondary data obtained through library research and journals as a review of the literature related to the Implementation of Shiddiq Characteristics in Implementing the GCG Transparency Principles. The results of this study will show the Implementation of Shiddiq's Characteristics in GCG Principles. As well as whether the implementation of GCG in Islamic financial institutions has fully complied with the principles of Islam in every factor as contained in the Al-Qura'n, Hadith, as well as the characteristics of akhlaqul karimah. The results of the literature study obtained will then be described and analyzed as well as the relationships, similarities and differences in research between one another in order to generate new ideas.